2015
DOI: 10.1038/ng.3176
|View full text |Cite
|
Sign up to set email alerts
|

High-density mapping of the MHC identifies a shared role for HLA-DRB1*01:03 in inflammatory bowel diseases and heterozygous advantage in ulcerative colitis

Abstract: Genome-wide association studies of the related chronic inflammatory bowel diseases (IBD) known as Crohn’s disease and ulcerative colitis have shown strong evidence of association to the major histocompatibility complex (MHC). This region encodes a large number of immunological candidates, including the antigen-presenting classical HLA molecules1. Studies in IBD have indicated that multiple independent associations exist at HLA and non-HLA genes, but lacked the statistical power to define the architecture of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
318
6
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(352 citation statements)
references
References 38 publications
24
318
6
4
Order By: Relevance
“…In this study, we have limited our participants to those who self-reported European ancestry and had both dietary assessment and genotype data for the rs12212067 polymorphism of the FOXO3 gene available. The rs12212067 polymorphism was genotyped using Immunochip, an Illumina iSelect HD custom genotyping array [30]. The study was conducted under ethical protocol MEC/04/12/011, authorised through the New Zealand Multi-Region Human Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we have limited our participants to those who self-reported European ancestry and had both dietary assessment and genotype data for the rs12212067 polymorphism of the FOXO3 gene available. The rs12212067 polymorphism was genotyped using Immunochip, an Illumina iSelect HD custom genotyping array [30]. The study was conducted under ethical protocol MEC/04/12/011, authorised through the New Zealand Multi-Region Human Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to CD, however, a prognostic UC association, widely replicated, exists-namely the HLA DRB*0103 association with extensive and severe disease ( 43,44 ). Th e allele frequency of this variant in the background population is ~4% rising to just over 10% in acute severe UC, limiting its utility as a stand-alone prognostic marker.…”
Section: Genetic Markers In Ucmentioning
confidence: 99%
“…Genetic variations in the HLA-DQA and HLA-DQB may affect the function of the antigen peptide binding groove of the protein [38]. A high-density typing of MHC region found multiple HLA-DRB1 alleles have equivalent association with HLA-DQA1 and HLA-DQB1 [39]. HLA-DRB1*04 is a risk factor for rheumatoid arthritis and is caused by variations of the peptide-binding groove [40].…”
Section: Major Histocompatibility Complexmentioning
confidence: 99%
“…HLA-DRB1*01:03 is associated with colonic CD. The risk variations of HLA-DRB1*0103 also showed a different 3D structure of the peptide-binding groove [39]. …”
Section: Major Histocompatibility Complexmentioning
confidence: 99%